2007
DOI: 10.1002/elps.200600740
|View full text |Cite
|
Sign up to set email alerts
|

Chiral CE of aromatic amino acids by ligand‐exchange with zinc(II)–L‐lysine complex

Abstract: A novel method of chiral ligand-exchange CE was developed with either L- or D-lysine (Lys) as a chiral ligand and zinc(II) as a central ion. This type of chiral complexes was explored for the first time to efficiently separate either individual pairs of or mixed aromatic amino acid enantiomers. Using a running buffer of 5 mM ammonium acetate, 100 mM boric acid, 3 mM ZnSO(4) x 7H(2)O and 6 mM L-Lys at pH 7.6, unlabeled D,L-tryptophan, D,L-phenylalanine, and D,L-tyrosine were well separated, giving a chiral reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
0
44
1
Order By: Relevance
“…It was also found that no separation occurred without L-proline, while the resolution was enhanced at Cu(II)/L-proline ratiosZ1:4. Our results showed clearly that the ratio of 1:2, which had been reported to be the most adequate for the chiral separation of T 4 enantiomers by LE-HPLC [6] and the enantiomeric separation of underivatized aminoacids using aqueous LE-CE and LE-HPLC [24][25][26][27][28][29], was not optimum in this case. Karbaum and Jira reported that the optimum ratio was 1:3 when using methanol as electrophoretic media for the LE-CE chiral separation of eight unmodified amino acids and concluded that the ratio of 1:2 was not optimal in nonaqueous media [30].…”
Section: Effect Of the Composition Of The Chiral Selector Complexmentioning
confidence: 62%
See 1 more Smart Citation
“…It was also found that no separation occurred without L-proline, while the resolution was enhanced at Cu(II)/L-proline ratiosZ1:4. Our results showed clearly that the ratio of 1:2, which had been reported to be the most adequate for the chiral separation of T 4 enantiomers by LE-HPLC [6] and the enantiomeric separation of underivatized aminoacids using aqueous LE-CE and LE-HPLC [24][25][26][27][28][29], was not optimum in this case. Karbaum and Jira reported that the optimum ratio was 1:3 when using methanol as electrophoretic media for the LE-CE chiral separation of eight unmodified amino acids and concluded that the ratio of 1:2 was not optimal in nonaqueous media [30].…”
Section: Effect Of the Composition Of The Chiral Selector Complexmentioning
confidence: 62%
“…The ratio of copper ions to L-proline was kept constant at 1:2, which was proved to be optimum for aqueous LE-CE and LE-HPLC according to the existing literature [6,[24][25][26][27][28][29]. Under our working conditions (15 mmol/L borate, pH 9.6), T 4 should be ionic with negative charges, since its pK a values are 2.1, 6.7 and 8.9 [3] and therefore, the analyte peaks should appear later than the EOF.…”
Section: Effect Of the Concentration Of Chiral Selector Complexmentioning
confidence: 99%
“…According to our previous study [28], Zn(II)-based CLE-CE was adopted for the direct analysis of aromatic AAs in Laozao's samples and the previously explored running buffer of 5 mM ammonium acetate, 100 mM boric acid, 3 mM ZnSO 4 ?7H 2 O, and 6 mM L-Lys (lysine) at pH 7.6 [28] was first tried by rechecking the critical parameters including buffering reagent, its concentration, pH, and especially the molar ratio of central ion-to-ligand, aiming at further improving the resolution and shortening the separation time. Unfortunately, the purpose did not achieved by just optimizing the known critical factors.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Because Cu(II) tends to adsorb onto silica capillary wall and has a fairly high UV absorption background, Mn(II), Co(II), Cd(II), and Ni(II) have been tried to replace the Cu(II) [27]. In our previous study, Zn(II) was used [28] and the related running conditions have been explored. We have then focused our efforts on assaying the AAs in Laozao and other foods.…”
Section: Introductionmentioning
confidence: 98%
“…The suitability of lysine complexes for the chiral separation of underivatized amino acids was introduced by Lu 24 for Cu(II) as central metal ion and by Qi 25 for Zn(II) complexes. To our knowledge there is no publication that deals with the enantioseparation of derivatized amino acids using this selector-ion system.…”
Section: Use Of L-lysine As Chiral Selectormentioning
confidence: 99%